MANAGEMENT OF USING SALINE IRRIGATION WATER AND TILLAGE SYSTEMS ON THE SOIL MECHANICAL AND HYDRAULIC - Shaima S. Dawod; Alaa S. Ati; Inas A. Abdujabbar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A field experiment was carried out within the Shanafiyah - Nasiriyah project / Iraq during the autumn season 2022-2023 to evaluate the performance of the different tillage systems in some soil physical and hydraulic properties when irrigated with salt water and 25% Leaching factor throughout the growing season. In addition to evaluating its performance in mechanical technical properties before sowing. The experiment included three systems: A. minimum tillage with a disc harrow b. Tillage with Chisel Plow and Spring Tooth Harrows c. Tillage with Mold Plow and Spring Tooth Harrows. The study results showed that the Mini Tillage with (Disk Harrow) treatment was superior in giving the best values ​​for the mechanical and technical properties and the soil’s physical and hydraulic properties compared to other systems.